Welcome to Westonci.ca, where your questions are met with accurate answers from a community of experts and enthusiasts. Experience the convenience of getting reliable answers to your questions from a vast network of knowledgeable experts. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Answer:
Please check the explanation.
Step-by-step explanation:
Completing table 1)
Given the function
y = -3x+2
put x = 3
y = -3(3)+2 = -9+2 = -7
so (x, y) = (3, -7)
Given the function
y = -3x+2
put x = 1
y = -3(1)+2 = -3+2 = -1
so (x, y) = (1, -1)
Given the function
y = -3x+2
put x = 0
y = -3(0)+2 = 0+2 = 2
so (x, y) = (0, 2)
Given the function
y = -3x+2
put x = -1
y = -3(-1)+2 = 3+2 = 5
so (x, y) = (-1, 5)
So the table becomes
x y = -3x+2 y (x, y)
3 y = -3(3)+2 -7 (3, -7)
1 y = -3(1)+2 -1 (1, -1)
0 y = -3(0)+2 2 (0, 2)
-1 y = -3(-1)+2 5 (-1, 5)
The graph of the equation y = -3x+2 is also attached below.
On the diagram, the red line represents the y = -3x+2 line.
Similarly,
Completing table 2)
Given the function
y = 2x+4
put x = 0
y = 2(0)+4=0+4 = 4
so (x, y) = (0, 4)
Given the function
y = 2x+4
put x = 1
y = 2(1)+4=2+4 = 6
so (x, y) = (1, 6)
Given the function
y = 2x+4
put x = 2
y = 2(2)+4=4+4 = 8
so (x, y) = (2, 8)
Given the function
y = 2x+4
put x = -1
y = 2(-1)+4=-2+4 = 2
so (x, y) = (-1, 2)
So the table becomes
x y = 2x+4 y (x, y)
0 y = 2(0)+4 4 (0, 4)
1 y = 2(1)+4 6 (1, 6)
2 y = 2(2)+4 8 (2, 8)
-1 y = 2(-1)+4 2 (-1, 2)
The graph of the equation y = 2x+4 is also attached below.
On the diagram, the blue line represents the y=2x+4 line.
We hope this was helpful. Please come back whenever you need more information or answers to your queries. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.